European survey on knowledge and attitudes of public health professionals on public health genomics: Pilot Study (Epidemiology, Biostatistics, and Public Health, 2022)
Background: During the past decade a debate has arisen on the possible utility of genomic science for public health purposes. Within this context, a survey is being conducted to assess attitudes of European public health (PH) professionals belonging to EUPHA network regarding their role in the implementation of public health genomics (PHG), and their knowledge and attitudes regarding genetic testing and the delivery of genetic services.Methods: A pilot on-line survey was conducted on professionals from Sapienza University of Rome and the Vrije University of Amsterdam. The survey tool is composed of 5 sections: Personal details, Professional activity, Knowledge on genetic testing and delivery of genetic services, Attitudes on genetic testing and delivery of genetic services, Attitudes on the role of PH professionals in PHG.Results: 34 people responded to the questionnaire, mostly medical doctors (61,8%). No respondents correctly identified all evidence-based applications of genetic testing. More than one third of respondents agreed that it would be more important to invest resources in the social and environmental causes of ill health than in genetic testing. Nearly 70% thought that PHG needs to be grounded on evidence of effectiveness, a lower rate agreed ii should be grounded on cost-effectiveness. The rate of agreement with the proposed roles of PH professionals in PHG was very high.Conclusions: This pilot study showed a positive attitude but the need to improve knowledge of PH professionals on PHG. It provided useful input for the implementation of the survey to all members of the EUPHA network.